Bacali F2011, variety of bread-baker wheat for cultivation in the ID 014, Colorado River - Alvarado Padilla, Jorge Iván; Camacho Casas, Miguel Alfonso; Chávez Vallalba, Gabriela; Figueroa López, Pedro; Ávila Casillas, Eva; Camarillo Pulido, Mario (Revista Mexicana de Ciencias Agrícolas, 2018)
Wheat is the main crop sown in the autumn-winter in Irrigation District 014 Río Colorado (ID 014), comprising the Valley of Mexicali, BC and San Luis Río Colorado, Sonora (Hernández et al., 2010). In the last f ive years (2008-2012) planting wheat in the ID 014 averaged 96 975 hectares (OEIDRUS, 2013), 83.9% corresponds to the Mexicali Valley, BC where between 2011 and 2013 were planted 12 085 hectares of bread-wheat (Triticum aestivum L.) varieties being Cachanilla F2000 with 37.4%, Yécora F70 with 22.9% and Rayon F89 with 9%. The Wheat Breeding Program of the Experimental Field Mexicali Valley of the National Research Institute of Forestry, Agriculture and Livestock (INIFAP), joining forces with the International Center for Maize and Wheat Improvement (CIMMYT), aims to generate genotypes various types of glutentoimprovetheprofitabilityandcompetitivenessofthe wheat crop by releasing varieties with yield, quality and health.
Keywords: competitiveness; gluten; profitability